Poetic Idea and Poetic Work - Girdzijauskas, Juozas (Problemos, 1986)
The author discusses the conception of poetic (artistic, aesthetic) idea as it is understood by the representatives of the classical German aesthetics (I. Kant, J. G. Fichte, F. Schelling, G. Hegel). The article deals with interrelations between poetic idea and poetic work. The role of poetic idea in the artistic whole of poetic work is shown by an analysis of S. Nėris’ poem “Klajūnelis” (“Wanderer”).